Repository of Scientific Texts of the National Academy of Sciences of Ukraine: Current Status and Development Prospects - Harahulia Serhii (Bìblìotečnij vìsnik)

(untitled)
The purpose of the article is to analyze the results of the implementation of the archive of academic periodicals as part of the Repository of Scientific Texts of the National Academy of Sciences of Ukraine, the state of integration and interoperability of the resource, and to substantiate the prospects for the further development of the Repository of Scientific Texts of the National Academy of Sciences of Ukraine. The research methodology combines analytical and synthetic processing of information, empirical research, and predictive modeling of the development of the research object. The scientific novelty of the articlelies in the fact that for the first time analyzed the state of implementation of one of the objects of the open science infrastructure of the National Academy of Sciences of Ukraine - the Repository of Open Texts of the National Academy of Sciences of Ukraine, which has been created in V. I. Vernadskyi National Library of Ukraine since 2023 with the aim of consolidating and unifying the presentation of information ona wide range of scientific publications that are the result of the scientific activity of the National Academy of Sciences of Ukraine, and is in the process of developing its resource and service components. The consolidated presentation of the entire corpus of academic periodicals in a single access point allows for the analysis of the inclusion of National Academy of Sciences of Ukraine journals in prestigious international databases of scientific information and to state the positive dynamics of the integration of academic journals into scientometric systems. Conclusions. The results of the research give grounds to assert the achievement of almost complete resource coverage of National Academy of Sciences of Ukraine journals in the Repository of Open Texts of the National Academy of Sciences of Ukraine and a high level of integration of Ukrainian academic periodicals into international scientific information systems. The developments made by the specialists of V. I. Vernadskyi National Library of Ukraine will allow the Repository of Open Texts of the National Academy of Sciences of Ukraine to become a full-fledged research information management system in the future, suitable for the correct reflection of the current state of development and integration of science, useful for researchers, publishers, analysts and administrators of scientific activity.